Criminal law in the common system of scientific knowledge: methodological aspect of criminal law research - Демидова, Людмила Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The author examines the science of criminal law as a part of the common system of scientific knowledge and offers her decisions of methodological problems of criminal law research. It is emphasized that the criminal law is an element of this system with reflection of integrational and differential processes that are inherent to the latter and to criminal law, in particular, with their characteristic accumulation, building and synthesis of knowledge. In this case, each criminal law research of problem issues of criminal law has become a new stage in the development of high-level scientific knowledge, to promote of improvement of the most important social values from criminal assault with embodiment of the principles of humanity and justice. Optimal approaches in the choice of methodological tools of the organization and implementation of the process of scientific knowledge are formulated. The author proved that the definition of methodological tools is caused by: (a) the purpose of research and tasks that are solved to achieve it, and elected its object and subject, and (b) the historical, theoretical, empirical and legal prerequisites, the establishment of which precedes the accumulation of new information about them. Research of problems of criminal law as scientific knowledge and its scientific result should be (a) reflect regularities that are established in the research on the object (subject), (b) take into account the theoretical achievements of research in the past and in the present period of criminal law (c) form and implement in accordance with the requirements imposed by such studies. The application of the new best-compositional approach in organizing and conducting criminal research that promotes comprehensive cognitive process and reflected by ordered structure of scientific work and its content are proposed.